Wasserstein distances, neuronal entanglement, and sparsity - Sawmya, Shashata; Kong, Linghao; Markov, Ilia; Alistarh, Dan-Adrian; Shavit, Nir (13th International Conference on Learning Representations)
Disentangling polysemantic neurons is at the core of many current approaches to interpretability of large language models. Here we attempt to study how disentanglement can be used to understand performance, particularly under weight sparsity, a leading post-training optimization technique. We suggest a novel measure for estimating neuronal entanglement: the Wasserstein distance of a neuron's output distribution to a Gaussian. Moreover, we show the existence of a small number of highly entangled "Wasserstein Neurons" in each linear layer of an LLM, characterized by their highly non-Gaussian output distributions, their role in mapping similar inputs to dissimilar outputs, and their significant impact on model accuracy. To study these phenomena, we propose a new experimental framework for disentangling polysemantic neurons. Our framework separates each layer's inputs to create a mixture of experts where each neuron's output is computed by a mixture of neurons of lower Wasserstein distance, each better at maintaining accuracy when sparsified without retraining. We provide strong evidence that this is because the mixture of sparse experts is effectively disentangling the input-output relationship of individual neurons, in particular the difficult Wasserstein neurons.

The journey matters: Average parameter count over pre-training unifies sparse and dense scaling laws - Jin, Tian; Humayun, Ahmed Imtiaz; Evci, Utku; Subramanian, Suvinay; Yazdanbakhsh, Amir; Alistarh, Dan-Adrian; Dziugaite, Gintare Karolina (13th International Conference on Learning Representations)
Pruning eliminates unnecessary parameters in neural networks; it offers a promising solution to the growing computational demands of large language models (LLMs). While many focus on post-training pruning, sparse pre-training--which combines pruning and pre-training into a single phase--provides a simpler alternative. In this work, we present the first systematic exploration of optimal sparse pre-training configurations for LLMs through an examination of 80 unique pruning schedules across different sparsity levels and training durations. We find that initiating pruning at 25% of total training compute and concluding at 75% achieves near-optimal final evaluation loss. These findings provide valuable insights for efficient and effective sparse pre-training of LLMs. Furthermore, we propose a new scaling law that modifies the Chinchilla scaling law to use the average parameter count over pre-training. Through empirical and theoretical validation, we demonstrate that this modified scaling law accurately models evaluation loss for both sparsely and densely pre-trained LLMs, unifying scaling laws across pre-training paradigms. Our findings indicate that while sparse pre-training achieves the same final model quality as dense pre-training for equivalent compute budgets, it provides substantial benefits through reduced model size, enabling significant potential computational savings during inference.

Cover Feature: Recessed microelectrodes as a platform to investigate the intrinsic redox process of Prussian blue analogs for energy storage application - Jiyane, Nomnotho; Santana Santos, Carla; Echevarria Poza, Igor; Palacios Corella, Mario; Abdillah Mahbub, Muhammad Adib; Marin‐Tajadura, Gimena; Quast, Thomas; Ibáñez, Maria; Ventosa, Edgar; Schuhmann, Wolfgang (Batteries & Supercaps)
he Cover Feature shows how recessed microelectrodes were employed as a versatile binder-free platform to investigate the electrochemical performance of Prussian Blue analogues (PBA), a class of promising battery materials, concerning capacity in varying aqueous electrolytes. To corroborate the micro-electrochemical findings, both ex-situ and operando chemical characterizations were conducted, offering complementary insights into the structural and chemical evolution of the PBA material during electrochemical cycling. More information can be found in the Research Article by W. Schuhmann and co-workers (DOI: 10.1002/batt.202400743).

Hoxb genes determine the timing of cell ingression by regulating cell surface fluctuations during zebrafish gastrulation - Moriyama, Yuuta; Mitsui, Toshiyuki; Heisenberg, Carl-Philipp J (Development)
During embryonic development, cell behaviors need to be tightly regulated in time and space. Yet how the temporal and spatial regulations of cell behaviors are interconnected during embryonic development remains elusive. To address this, we turned to zebrafish gastrulation, the process whereby dynamic cell behaviors generate the three principal germ layers of the early embryo. Here, we show that Hoxb cluster genes are expressed in a temporally collinear manner at the blastoderm margin, where mesodermal and endodermal (mesendoderm) progenitor cells are specified and ingress to form mesendoderm/hypoblast. Functional analysis shows that these Hoxb genes regulate the timing of cell ingression: under- or overexpression of Hoxb genes perturb the timing of mesendoderm cell ingression and, consequently, the positioning of these cells along the forming anterior-posterior body axis after gastrulation. Finally, we found that Hoxb genes control the timing of mesendoderm ingression by regulating cellular bleb formation and cell surface fluctuations in the ingressing cells. Collectively, our findings suggest that Hoxb genes interconnect the temporal and spatial pattern of cell behaviors during zebrafish gastrulation by controlling cell surface fluctuations.

L∞-optimal transport of anisotropic log-concave measures and exponential convergence in Fisher’s infinitesimal model - Khudiakova, Kseniia; Maas, Jan; Pedrotti, Francesco (The Annals of Applied Probability)
We prove upper bounds on the L∞-Wasserstein distance from optimal transport between strongly log-concave probability densities and log-Lipschitz perturbations. In the simplest setting, such a bound amounts to a transport-information inequality involving the L∞-Wasserstein metric and the relative L∞-Fisher information. We show that this inequality can be sharpened significantly in situations where the involved densities are anisotropic. Our proof is based on probabilistic techniques using Langevin dynamics. As an application of these results, we obtain sharp exponential rates of convergence in Fisher’s infinitesimal model from quantitative genetics, generalising recent results by Calvez, Poyato, and Santambrogio in dimension 1 to arbitrary dimensions.

When is liquid democracy possible?: On the manipulation of variance - Chatterjee, Krishnendu; Gilbert, Seth; Schmid, Stefan; Svoboda, Jakub; Yeo, Michelle X (Proceedings of the ACM Symposium on Principles of Distributed Computing)
Liquid democracy is a transitive vote delegation mechanism over voting graphs. It enables each voter to delegate their vote(s) to another better-informed voter, with the goal of collectively making a better decision. The question of whether liquid democracy outperforms direct voting has been previously studied in the context of local delegation mechanisms (where voters can only delegate to someone in their neighbourhood) and binary decision problems. It has previously been shown that it is impossible for local delegation mechanisms to outperform direct voting in general graphs. This raises the question: for which classes of graphs do local delegation mechanisms yield good results? In this work, we analyse (1) properties of specific graphs and (2) properties of local delegation mechanisms on these graphs, determining where local delegation actually outperforms direct voting. We show that a critical graph property enabling liquid democracy is that the voting outcome of local delegation mechanisms preserves a sufficient amount of variance, thereby avoiding situations where delegation falls behind direct voting1. These insights allow us to prove our main results, namely that there exist local delegation mechanisms that perform no worse and in fact quantitatively better than direct voting in natural graph topologies like complete, random d-regular, and bounded degree graphs, lending a more nuanced perspective to previous impossibility results.

Reaction precursor-mediated formation of stable supercrystals in colloidal nanocrystal synthesis: PbTe case - Lee, Seungho; Balazs, Daniel; Horta, Sharona; Rayaroth Puthiyaveettil, Aiswarya; Ibáñez, Maria (Proceedings of the MATSUS Spring 2025 Conference)
Supercrystals represent three-dimensional orderings of colloidal nanocrystals (NCs), showcasing collective properties in photonics, phononics, and electronics applications.1,2 Recent studies have shown that such assemblies are directly produced during nanocrystal reactions.3–6 However, a fundamental understanding of in situ formed supercrystals that withstand typical NC purification processes remains underexplored, which is important for further use. Herein, we report the reaction precursor-mediated formation of stable PbTe supercrystals. Rationalizing the formation of these assemblies through small-angle x-ray scattering (SAXS) measurements, we unveil their formation mechanism. Our findings reveal that the supercrystal formation occurs in the presence of an excess of lead oleates in the crude solution. It should be noted that the formed supercrystals can be stabilized under specific conditions determined by the lead oleate cluster concentration, content of trioctylphosphine telluride (TOP-Te), NC size and the need of an annealing step at mild conditions. Furthermore, this approach allows for the continuous growth of a secondary phase within the supercrystal; for example in the case of PbTe supercrystals, a PbS shell can be grown on each PbTe NC constituent, resulting in core-shell PbTe-PbS supercrystals. Our work elucidates that reaction precursors play an important role in in situ SC formation and stabilization, implying the possibility of applying this knowledge to other NC reactions.

Human microglia impact neuronal development in retinal organoids - Hübschmann, Verena
Prenatal immune challenges pose significant risks to human embryonic brain and eye development. However, we still lack knowledge about the safe usage of anti-inflammatory drugs during pregnancy. Human induced pluripotent stem cell (hIPSC)-derived brain organoid models provide a unique opportunity to investigate neuronal development and have started to explore functional consequences upon viral infection. However, brain organoids usually lack microglia, the brain-resident immune cells. They are present in the early human embryonic brain and actively participate in neuronal circuit development. At the same time, microglia are known for their immune-sensing properties and will influence viral-mediated effects. In my thesis, I was interested to study the multifunctional role of human microglia during retinal development. In chapter 1, I characterize the innate occurrence of IBA1+-microglia-like cells within the retinal organoid differentiation (Bartalska et al., 2022). Therefore, we differentiate hIPSC using an unguided retinal organoid differentiation protocol and observe the presence of IBA1+-microglia-like cells alongside retinal cups between week 3 and 4 in 2.5D culture. However, instead of infiltrating the neuroectodermal sides, they enrich within non-pigmented, 3D-cystic compartments that develop in low numbers parallel to 3D-retinal organoids. To enrich for IBA1+-microglia precursors (preMG), we guided the differentiation with a low-dosed BMP4 application, which prevents retinal cup development and enhances microglia and 3D-cysts formation. We characterize the differentiated preMG for their microglia-like identity and validated their functionality. In parallel, mass spectrometry identifies the 3D-cysts to express mesenchymal and epithelial markers. We confirm that comparable 3D-cysts are also the preferential environment for IBA1+-microglia-like cells within the unguided retinal organoid differentiation. In chapter 2, I investigate how microglia influence retinal development and whether they contribute to viral-mediated consequences (Schmied et al., 2025). Here, we assemble preMG, which we have characterized in chapter 1, into 3D-retinal organoids. Once the outer plexiform layer forms, microglia-like cells (iMG) populate them and interact with retinal cell types. However, at this developmental stage, the ganglion cell number decreases in 3D-retinal organoids. Thus, we adapted the model into 2D which promotes their survival. Integrated iMG engulf ganglion cells and control their cell number. In parallel, we apply the immunostimulant POLY(I:C) to mimic a fetal viral infection. Although POLY(I:C) stimulation affects iMG phenotype, it does not influence their interaction with ganglion cells. Furthermore, iMG presence significantly contributes to the supernatant’s inflammatory secretome and increases retinal cell proliferation. Simultaneous exposure to the non-steroidal anti-inflammatory drug (NSAID) ibuprofen dampens POLY(I:C)-mediated consequences of the iMG phenotype and ameliorates cell proliferation. Remarkably, while POLY(I:C) disrupts neuronal calcium dynamics independent of iMG presence, ibuprofen rescues this effect only in the presence of iMG. Mechanistically, ibuprofen blocks the enzymes cyclooxygenase 1 and 2 (COX1/ PTGS1 and COX2/ PTGS2) simultaneously, from which iMG predominantly express COX1. Selective inhibition of COX1 does not restore the calcium peak amplitude upon POLY(I:C) stimulation, indicating ibuprofen’s effect depends on the presence and interplay of both, COX1 and COX2. In summary, we characterized the 3D-retinal organoid model for the occurrence of IBA1+-microglia like cells. As the innately developing IBA1+-cells enrich in mesenchymal over retinal structures, we optimized a protocol to differentiate IBA1+-microglia precursors. By combining these two models we generate microglia-assembled retinal organoids. Our results underscore the importance of microglia during neurodevelopment, in the context of prenatal immune challenges and provide insight into the mechanisms by which ibuprofen exerts its protective effects during embryonic development.

Ancestral origin and functional expression of a hyaluronic acid pathway complement in mussels - Rosani, Umberto; Altan, Nehir; Venier, Paola; Bortoletto, Enrico; Volpi, Nicola; Bernecky, Carrie A (Biology)
Hyaluronic acid (HA) is a key extracellular matrix component of vertebrates, where it mediates cell adhesion, immune regulation, and tissue remodeling through its interaction with specific receptors. Although HA has been detected in a few invertebrate species, the lack of fundamental components of the molecular HA pathway poses relevant objections about its functional role in these species. Mining genomic and transcriptomic data, we considered the conservation of the gene locus encoding for the extracellular link protein (XLINK) in marine mussels as well as its expression patterns. Structural and phylogenetic analyses were undertaken to evaluate possible similarities with vertebrate orthologs and to infer the origin of this gene in invertebrates. Biochemical analysis was used to quantify HA in tissues of Mytilus galloprovincialis. As a result, we confirm that the mussel can produce HA (up to 1.02 ng/mg in mantle) and that its genome encodes two XLINK gene loci. These loci are conserved in Mytilidae species and show a complex evolutionary path. Mussel XLINK genes appeared to be expressed during developmental stages in three mussel species, ranking in the top 100 expressed genes in M. trossulus at 17 h post-fertilization. In conclusion, the presence of HA and an active gene with the potential to bind HA suggests that mussels have the potential to synthesize and use HA and are among the few invertebrates encoding this gene.

LINC01638 promotes epithelial-to-mesenchymal transition in endometriosis epithelial cells by up-regulating RHOB via HDAC1 suppression - Yotova, Iveta; Proestling, Katharina; Pauler, Florian; Rainer, Lisa; Kaup, Leonie; Heine, Jana; Sandrieser, Lejla; Wenzl, René; Hudson, Quanah J. (Reproductive Biomedicine Online)
Research question: Is LINC01638 involved in regulation of epithelial-to-mesenchymal transition (EMT) in endometriosis? Design: A prospective patient cohort study was combined with functional experiments in the 12Z endometriosis epithelial cell line to investigate the role of LINC01638 in endometriosis. Eutopic endometrial samples were collected by curettage, and ectopic endometrial lesion samples were collected by laparoscopic surgery from 24 control patients and 41 patients with endometriosis. The phenotype of 12Z cells was assessed following LINC01638 knockdown using siRNA, performing proliferation, adhesion, migration and invasion assays, as well as assessing apoptosis and cell cycle changes with flow cytometry assays. In order to assess the relationship between LINC01638 and histone deacetylase class 1 enzyme (HDAC1), LINC01638 knockdown was combined with HDAC inhibition with the specific HDAC inhibitor romidepsin. Results: LINC01638 was up-regulated in the epithelial layer of endometriotic lesions, and LINC01638 knockdown in 12Z cells led to reduced proliferation, adhesion, migration and invasion. The reduction in proliferation was associated with increased p21 and p27 expression, and G1 phase arrest. Further analysis of LINC01638 control and knockdown cells revealed that a number of transcription factors associated with EMT are down-regulated in knockdown cells, along with the cytoskeleton regulatory gene RHOB, while HDAC1 was up-regulated. Chromatin immunoprecipitation analysis and HDAC1 inhibitory treatment combined with LINC01638 knockdown indicated that LINC01638 regulates RHOB expression via HDAC1-mediated promoter deacetylation. RHOB is up-regulated in the epithelial layer of endometriotic lesions compared with eutopic endometrium, supporting a role in the disease. Conclusions: LINC01638 is an epigenetic regulator of the pathogenesis of endometriosis, promoting proliferation and EMT of endometriotic lesions.

Dual role of pectin methyl esterase activity in the regulation of plant cell wall biophysical properties - Gallemi, Marçal; Montesinos López, Juan C; Zarevski, Nikola; Pribyl, Jan; Skládal, Petr; Hannezo, Edouard B; Benková, Eva (Frontiers in Plant Science)
Introduction: Acid-growth theory has been postulated in the 70s to explain the rapid elongation of plant cells in response to the hormone auxin. More recently, it has been demonstrated that activation of the proton ATPs pump (H+-ATPs) promoting acidification of the apoplast is the principal mechanism by which auxin and other hormones such as brassinosteroids (BR) induce cell elongation. Despite these advances, the impact of this acidification on the mechanical properties of the cell wall remained largely unexplored. Methods: Here, we use elongation assays of Arabidopsis thaliana hypocotyls and Atomic Force Microscopy (AFM) to correlate hormone-induced tissue elongation and local changes in cell wall mechanical properties. Furthermore, employing transgenic lines over-expressing Pectin Methyl Esterase (PME), along with calcium chelators, we investigate the effect of pectin modification in hormone-driven cell elongation. Results: We demonstrate that acidification of apoplast is necessary and sufficient to induce cell elongation through promoting cell wall softening. Moreover, we show that enhanced PME activity can induce both cell wall softening or stiffening in extracellular calcium dependent-manner and that tight control of PME activity is required for proper hypocotyl elongation. Discussion: Our results confirm a dual role of PME in plant cell elongation. However, further investigation is needed to assess the status of pectin following short- or long-term PME treatments in order to determine if pectin methyl-esterification might promote its degradation as well as the role of PME inhibitors upon PME induction.

Migrating immune cells globally coordinate protrusive forces - Dos Reis Rodrigues, Patricia; Avellaneda Sarrió, Mario; Canigova, Nikola; Gärtner, Florian R; Vaahtomeri, Kari; Riedl, Michael; De Vries, Ingrid; Merrin, Jack; Hauschild, Robert; Fukui, Yoshinori; Juanes Garcia, Alba; Sixt, Michael K (Nature Immunology)
Efficient immune responses rely on the capacity of leukocytes to traverse diverse and complex tissues. To meet such changing environmental conditions, leukocytes usually adopt an ameboid configuration, using their forward-positioned nucleus as a probe to identify and follow the path of least resistance among pre-existing pores. We show that, in dense environments where even the largest pores preclude free passage, leukocytes position their nucleus behind the centrosome and organelles. The local compression imposed on the cell body by its surroundings triggers assembly of a central F-actin pool, located between cell front and nucleus. Central actin pushes outward to transiently dilate a path for organelles and nucleus. Pools of central and front actin are tightly coupled and experimental depletion of the central pool enhances actin accumulation and protrusion formation at the cell front. Although this shifted balance speeds up cells in permissive environments, migration in restrictive environments is impaired, as the unleashed leading edge dissociates from the trapped cell body. Our findings establish an actin regulatory loop that balances path dilation with advancement of the leading edge to maintain cellular coherence.

Cell-specific wiring routes information flow through hippocampal CA3 - Watson, Jake; Vargas Barroso, Victor M; Jonas, Peter M (Cell Reports)
The hippocampus, critical for learning and memory, is dogmatically described as a trisynaptic circuit where dentate gyrus granule cells (GCs), CA3 pyramidal neurons (PNs), and CA1 PNs are serially connected. However, CA3 also forms an autoassociative network, and its PNs have diverse morphologies, intrinsic properties, and GC input levels. How PN subtypes compose this recurrent network is unknown. To determine the synaptic arrangement of identified CA3 PNs, we combine multicellular patch-clamp recording and post hoc morphological analysis in mouse hippocampal slices. PNs can be divided into distinct “superficial” and “deep” subclasses, the latter including previously reported “athorny” cells. Subclasses have distinct input-output transformations and asymmetric connectivity, which is more abundant from superficial to deep PNs, splitting CA3 locally into two parallel recurrent networks. Coincident spontaneous inhibition occurs frequently within but not between subclasses, implying subclass-specific inhibitory innervation. Our results suggest two separately controlled sublayers for parallel information processing in hippocampal CA3.

Phenotypic divergence and genomic architecture between parallel ecotypes at two different points on the speciation continuum in a marine snail - Raffini, Francesca; De Jode, Aurélien; Johannesson, Kerstin; Faria, Rui; Zagrodzka, Zuzanna B.; Westram, Anja M; Galindo, Juan; Rolán-Alvarez, Emilio; Butlin, Roger K. (Molecular Ecology)
Speciation is rarely observable directly. A way forward is to compare pairs of ecotypes that evolved in parallel in similar contexts but have reached different degrees of reproductive isolation. Such comparisons are possible in the marine snail Littorina saxatilis by contrasting barriers to gene flow between parallel ecotypes in Spain and Sweden. In both countries, divergent ecotypes have evolved to withstand either crab predation or wave action. Here, we explore transects spanning contact zones between the Crab and the Wave ecotypes using low-coverage whole-genome sequencing, morphological and behavioural traits. Despite parallel phenotypic divergence, distinct patterns of differentiation between the ecotypes emerged: a continuous cline in Sweden indicating a weak barrier to gene flow, but two highly genetically and phenotypically divergent, and partly spatially overlapping clusters in Spain suggesting a much stronger barrier to gene flow. The absence of Spanish early-generation hybrids supported strong isolation, but a low level of gene flow is evident from molecular data. In both countries, highly differentiated loci were located in both shared and country-specific chromosomal inversions but were also present in collinear regions. Despite being considered the same species and showing similar levels of phenotypic divergence, the Spanish ecotypes are much closer to full reproductive isolation than the Swedish ones. Barriers to gene flow of very different strengths between ecotypes within the same species might be explained by dissimilarities in the spatial arrangement of habitats, the selection gradients or the ages of the systems.

The role of dynamin related protein 2A in cytokinin regulated plant growth and development - Wang, Yiqun

Structural properties of games on graphs - Svoboda, Jakub
The evolution shapes the world around us. Not only in biology, where the fittest individuals spread their genes but also in physics and social dynamics, the evolutionary forces determine the development of a state of matter or public opinions. Many models describe these dynamics. This thesis examines the role of the structure in the models of selection. The population structure is represented as a graph or a network, and each vertex is occupied by one individual. Every individual has a type and fitness that represents the reproductive potential and depends on the type, occupied vertex, and the arrangement of the neighbors. The evolution is modeled in discrete steps; in one step, one individual is replaced by a neighbor selected randomly with the influence of fitness. The role of the networks is widely examined in the literature. The structures that promote the spread of the desired type compared to the structureless case are called amplifiers. The existence of amplifiers in various settings is an intensively studied topic, and in some settings, the amplifiers have been identified. Moreover, there are other important questions about the number of steps until one type spreads over the whole network (fixation time), the computational complexity, and the questions about the robustness of these processes. This thesis explores the role of structure in evolution from many perspectives. First, it introduces different models and various choices that can be made in the models of evolution. It highlights the role of the structure in the real world and how this is reflected in these models. Then, it describes the previous results and open problems. Second, the thesis describes an amplifier for two variants of the Moran process: one with a constant birth rate and the other with a constant death rate. This is an important contribution to the robustness of the amplification. Third, the thesis determines the complexity of spatial games. These are processes where the fitness comes from a game, and the strength of selection is high. It shows that determining the fate of cooperation in these games is a PSPACE-complete problem. Fourth, the thesis describes the amplifier of cooperation for spatial games. This is the first amplifier in this setting. Fifth, the thesis examines the coexistence in the Moran process with environmental heterogeneity. In this setting, the fitness depends not only on the type of the individual but also on the occupied vertex. The chapter determines the relationship between the interactions of vertices of different types and the coexistence time. Sixth, the thesis examines the social balance on networks and proposes a stochastic dynamic partially aware of the state of the graph, which reaches a balanced position quickly. Finally, the thesis presents conclusions and outlines the directions for future work.

Catalogue of criteria for assessing the funding eligibility of Open Science infrastructures - Gredler, Paul; Kaier, Christian; Danowski, Patrick; Zoyer, Michael; Rieck, Katharina; Ferus, Andreas; Rosenberger, Elisabeth; Löffler, Alexander; Hofer, Lisa; Still, Laura
This criteria catalogue and the accompanying assessment questions were developed by a working group of KEMÖ (Kooperation E-Medien Österreich, the Austrian Academic Library Consortium). They are intended to support research institutions and organisations in the evaluation of Open Science Infrastructures. The 20 criteria outlined in the catalogue provide a structured basis for making informed decisions regarding the financial support of these infrastructures. The assessment questions are intended to be completed by Open Science Infrastructures and can be shared with them accordingly.

A monitoring-oriented theory and classification of quantitative specifications - Sarac, Naci E
Quantitative properties offer a framework for specifying and verifying system behaviors beyond the traditional boolean perspective. For example, while a boolean property may specify whether a server eventually grants every request it receives, a quantitative one may map each server execution to its average response time. This quantitative view is relatively well-studied in the context of static verification. However, although such properties often appear in practice as performance or robustness measures in a dynamic verification context, a general theoretical framework for their analysis and classification from a monitoring perspective is still missing. In this thesis, we aim to develop such a framework that takes resource-precision tradeoffs of monitors as a central consideration. We present the first theory of monitorability for quantitative properties where monitors can be naturally approximate and compared regarding their precision and resource use. In particular, we show that additional monitor resources such as registers or states lead to strictly better approximations for some properties. To enable such analyses in a machine-model independent way, we describe an abstract notion of monitors that can be instantiated with concrete models of monitors. Within this framework, we study how abstract monitors behave and identify classes of properties amenable to approximate monitoring with resource-precision considerations. We then extend the boolean safety-liveness dichotomy and safety-progress hierarchy to the quantitative setting with a monitoring perspective. In particular, we prove that every property is the pointwise minimum of a safety property and a liveness property, and properties that are both safe and co-safe can be approximately monitored arbitrarily precisely using only finitely many states. We also study the classes of quantitative properties definable by finite-state quantitative automata and provide algorithms for deciding their safety or liveness as well as their safety-liveness decompositions. Finally, we present the first general-purpose tool for automating the analysis, verification, and monitoring of quantitative automata. -------------------------------------------------------------------------------------------------------------------------------------------------------------- In reference to IEEE copyrighted material which is used with permission in this thesis, the IEEE does not endorse any of ISTA's products or services. Internal or personal use of this material is permitted. If interested in reprinting/republishing IEEE copyrighted material for advertising or promotional purposes or for creating new collective works for resale or redistribution, please go to http://www.ieee.org/publications_standards/publications/rights/rights_link.html to learn how to obtain a License from RightsLink.

Coordination of protrusive forces in immune cell migration - Dos Reis Rodrigues, Patricia
Immune responses depend on the coordinated and efficient migration of leukocytes. These cells, which are embedded and tightly confined within tissues, must navigate and traverse diverse and complex three-dimensional environments. Leukocytes adapt their locomotory behavior to the mechanical, geometrical, and biochemical characteristics of their surroundings. In low-density environments, where the pore size of the interstitial matrix allows free passage, these cells position the nucleus directly behind the lamellipodium, the protrusive actin structure that forms the leading front of the cell. In this configuration, they use the nucleus as a gauge to identify the path of least resistance. Here, we show that in high-density environments, where the pore size precludes free passage of the cell body, leukocytes reposition the microtubule-organizing center (MTOC) and associated organelles in front of the nucleus. In this configuration, they use actin structures protruding orthogonally to the direction of migration in order to open a path for the cell body. We identify two distinct actin populations that serve this purpose at different subcellular localizations. At the leading edge, local indentation of the plasma membrane leads to recruitment of the Wiskott-Aldrich syndrome protein (WASp), which, via Arp2/3, results in the formation of individual actin foci. At the cell body, actin polymerization is triggered by DOCK8, a Cdc42 exchange factor, resulting in the formation of a central actin pool. We demonstrate that the central and peripheral actin pools are functionally communicating and that depletion of the central actin pool leads to increased actin accumulation at the cell front, resulting in excessive extension of the leading edge.

The ER complex SUTU-7/MACO-1 regulates the fate of mRNAs encoding GPCRs - Schön, Hanna